Multi-Disciplinary Management of Athletes with Post-Concussion Syndrome: An Evolving Pathophysiological Approach - Ellis, Michael J.; Leddy, John; Willer, Barry (Frontiers in Neurology, 2016)
Historically, patients with sports-related concussion (SRC) have been managed in a uniform fashion consisting mostly of prescribed physical and cognitive rest with the expectation that all symptoms will spontaneously resolve with time. Although this approach will result in successful return to school and sports activities in the majority of athletes, an important proportion will develop persistent concussion symptoms characteristic of post-concussion syndrome (PCS). Recent advances in exercise science, neuroimaging, and clinical research suggest that the clinical manifestations of PCS are mediated by unique pathophysiological processes that can be identified by features of the clinical history and physical examination as well as the use of graded aerobic treadmill testing. Athletes who develop PCS represent a unique population whose care must be individualized and must incorporate a rehabilitative strategy that promotes enhanced recovery of concussion-related symptoms while preventing physical deconditioning. In this review, we present our evolving evidence-based approach to evaluation and management of athletes with PCS that aims to identify the pathophysiological mechanisms mediating persistent concussion symptoms and guides the initiation of individually tailored rehabilitation programs that target these processes. In addition, we outline the important qualified roles that multi-disciplinary healthcare professionals can play in the management of this patient population, and discuss where future research efforts must be focused to further evaluate this evolving pathophysiological approach.